Optimizing Anthocyanin Yield and Stability from Black Rice Bran through Response Surface Methodology and Microencapsulation - Pimsuwan, Patcharamon; Khattiya, Suphamath; Kanha, Nattapong; Laokuldilok, Thunnop (Journal of Food Health and Bioenvironmental Science, 2024)
Black rice bran is a rich source of bioactive compounds, particularly anthocyanins, which offer significant health benefits and are thus suitable for development into high-value products. However, anthocyanins are prone to degradation due to environmental factors. The objectives of this research were to study the extraction and encapsulation of anthocyanins using spray drying. Anthocyanin extraction from black rice bran was optimized using response surface methodology with a Box-Behnken design. Additionally, the parameters for spray-dried microcapsule production, including wall materials and inlet air, were investigated. Three key factors for the extraction of anthocyanin from black rice bran involved varying citric acid concentrations (1-4%), temperatures (40-90 °C) and time (30-180 min). The optimal conditions providing maximum total anthocyanin content emerged as a 4% citric acid concentration, a temperature of 74.66 °C and an extraction time of 37.24 min. Under these conditions, the resulting extract exhibited a total anthocyanin content of 70.70 mg/L. Microencapsulation using maltodextrin and Arabic gum at air temperatures of 160 °C, 170 °C and 180 °C produced microcapsules with low moisture content (5.37%-6.23%), water activity (0.38-0.48) and high encapsulation efficiency (94.25%-98.50%). These microcapsules exhibited substantial antiradical properties, with 2,2-Diphenyl-1-picrylhydrazyl (DPPH) scavenging activity and ferric reducing antioxidant power (FRAP) values ranging between 6.90% to 10.11% and 20.82 to 35.51 mg Trolox equivalent (TE)/g, respectively. Maltodextrin at 160 °C exhibited the greatest solubility and lowest wettability. The findings of this study offer valuable insights into the extraction and future application of anthocyanin extracts derived from black rice bran in powder form.